Reputation, Renegotiation, and the Choice between Bank Loans and Publicly Traded Debt - Chemmanur, Thomas J.; Fulghieri, Paolo (Review of Financial Studies, 1994)
We model firms' choice between bank loans and publicly traded debt, allowing for debt renegotiation in the event of financial distress. Entrepreneurs, with private information about their probability of financial distress, borrow from banks (multiperiod players) or issue bonds to implement projects. If a firm is in financial distress, lenders devote a certain amount of resources (unobservable to entrepreneurs) to evaluate whether to liquidate the firm or to renegotiate its debt. We demonstrate that banks' desire to acquire a reputation for making the 'right' renegotiation versus liquidation decision provides them an endogenous incentive to devote a larger amount of resources than bondholders toward such evaluations. In equilibrium, bank loans dominate bonds from the point of view of minimizing inefficient liquidation,. however, firms with a lower probability of financial distress choose bonds over bank loans.